PENEGAKAN HUKUM TINDAK PIDANA PROSTITUSI ONLINE DI SURABAYA - Kurniadi Prasetyo (Esensi Hukum, 2020)
Abstract The prostitution crime in Indonesia, especially in Surabaya, is getting higher. With the closure of Dolly's prostitution area, the providers of prostitus services use the internet to open their services. The use of the internet as a prostitution service is often called online prostitution. Problems regarding the crime of online prostitution in Surabaya are regulated in article 27 paragraph (1) of Law no. 11 of 2008 concerning Information and Electronic Transactions; Article 45 paragraph (1) of Law No. 19 of 2016 concerning Information and Electronic Transactions; Article 27 Paragraph (1) Law No. 1 of 2018 concerning Electronic Information and Transactions; Article 4 paragraph (2) of Law No. 44 of 2008 concerning Pornography; Article 4 paragraph (2) of Law No. 44 of 2008 concerning Pornography; article 296 of the Criminal Code; Article 506 of the Criminal Code; Article 37 paragraph (2) of Surabaya City Government Regulation No. 2 of 2014 concerning Implementation of Public Order and Community Peace. In law enforcement, online prostitution crime in Surabaya does not only tend to impose sanctions in accordance with article 27 paragraph (1) of the Information and Electronic Transaction Law. However, the City Government of Surbaya is trying to implement prevention of trafficking in persons suspected of having links to online prostitution. In the policy to prevent trafficking in persons, the Surabaya city government has implemented two prevention systems, namely Preemtif Prevention and Preventive Prevention. Keywords: Criminal Act, Online Prostitution, Law Enforcement Abstrak Tindak pidana prostitusi di Indonesia khususnya di Surabaya semakin tinggi. Dengan ditutupnya kawasan prostitusi Dolly membuat para penyedia jasa prostitusi menggunakan media internet untuk membuka jasanya. Penggunaan internet sebagai layanan jasa prostitusi sering kali disebut prostitusi online. Permasalahan mengenai tindak pidana prostitusi online di Surabaya diatur dalam Pasal 27 ayat (1) Undang-Undang No. 11 Tahun 2008 tentang Infomarsi dan Transaksi Elektornik; Pasal 45 ayat (1) Undang-Undang No. 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik; Pasal 27 ayat (1) Undang-Undang No. 1 Tahun 2018 tentang Informasi dan Transaksi Elektronik; Pasal 4 ayat (2) Undang-Undang No. 44 Tahun 2008 Tentang Pornografi; Pasal 4 ayat (2) Undang-Undang No. 44 Tahun 2008 Tentang Pornografi; Pasal 296 KUHP; Pasal 506 KUHP; Pasal 37 ayat (2) Peraturan Daerah Pemerintahan Kota Surabaya No. 2 Tahun 2014 tentang Penyelenggaraan Ketertiban Umum dan Ketentraman Masyarakat. Dalam penegakan hukum tindak pidana prostitusi online di Surabaya tidak hanya cenderung dengan memberikan sanksi sesuai dengan Pasal 27 ayat (1) Undang-Undang Informasi dan Transaksi Elektronik. Namun Pemerintah Kota Surabaya mencoba menerapkan pencegahan terhadap tindak pidana perdagangan orang yang dinilai mempunyai keterkaitan dengan tindak pidana prostitusi online. Dalam kebijakan pencegahan tindak pidanak perdagangan orang Pemerintah Kota Surabaya menerapkan dua sistem pencegahan yaitu pencegahan preemtif dan pencegahan preventif. Kata Kunci: Tindak Pidana, Prostitusi Online, Penegakan Hukum